Assessing strategies to increase efficiency of renewable gas production from feedlot collected manure - Makowski, Veronika Agata, author; Sharvelle, Sybil, advisor; Bareither, Chris, committee member; Carvalho, Pedro, committee member (Colorado State University. Libraries, 2025)
Anaerobic digestion (AD) is a widely used method for converting organic waste into renewable natural gas in the form of methane, but its effectiveness is limited when processing feedlot manure due to the presence of inorganic particles. These particles, such as sand, cause operational challenges. Here, an integrated system is assessed that includes pre-treatment of feedlot manure and processing in a continuously stirred reactor with liquid extraction to maintain higher solids. The extracted liquid is assessed for potential digestion in a high-rate fixed film reactor. The integrated system evaluated is called High-Rate Hybrid Continuously Stirred AD Reactor (CSTR). This study aims to evaluate the performance of multiple completely mixed AD reactors under varying solids concentrations to simulate the key components of the High-Rate Hybrid Continuously Stirred AD Reactor (CSTR) System. The system is divided into two phases where phase 1 includes pretreatment to remove problematic inorganic materials and preparing high solids content manure slurries that prevent solids from settling. Phase two includes maintaining a high solids content within the operational CSTR AD reactors, analyzing the methanogenic potential of the manure slurry and removed liquid as well as impact to particle settling, and integrating water removal for delivery to a high-rate fixed-film reactor. The goal of CSTR AD operation is to maintain higher solids content in the digesters while preventing the settling of sand and other inorganic particles. To achieve this, extensive pretreatment methods for removing large particles, particularly sand, and creating the influent manure slurries are utilized. To determine an efficient influent, even after pretreatment, manure slurries with different total solids (TS) concentrations (5% and 8%) were examined to assess their effects on viscosity, particle settling behavior, and methane production throughout and post the operational reactor run. After the operational reactor run, filtered liquid digestate was analyzed for biochemical methane potential (BMP) in order to determine the total potential methane yield of each manure slurry concentration within the reactors. By comparing the settling and viscosity characteristics and biogas yields across these concentrations, the research aimed to determine an optimal TS% for manure slurry in AD applications. The results from this analysis determined that a higher TS%, 8% TS, proved to demonstrate more consistent viscosities, slower settling velocities, and significantly higher methane yields. The 8% TS reactors produced 170.2 mL of methane (CH4/ g VS feedstock) versus 82.2 mL (CH4/ g VS feedstock) for the 5% TS. Cumulative methane production from the BMP reactors approached 200 mL of methane (CH4/ g VS feedstock) versus 150 mL of methane (CH4/ g VS feedstock) for 5% TS. After the settling analysis, the VS% of the settled layers for 8% TS ranged from 35 to 55%, with the top layers being of similar VS%, keeping most material in suspension. While 5% TS ranged from 48 to 52%, demonstrating that both inorganic and material settled out of suspension. The findings of this research contribute to improving AD efficiency and sustainability by enhancing feedstock suitability and maximizing methane generation.
Keywords: integrated; pretreatment; inorganic material; renewable natural gas; methane production